أسلوب التحسين المستمر كأداة استراتيجية فعالة للحصول علي ميزة تنافسية: CONTINUOUS IMPROVEMENT METHOD AS AN EFFECTIVE STRATEGIC TOOL TO INCREASE THE COMPETITIVE ADVANTAGE - Elgool, Zedan Mohamed Ibrahim; Lubis, Asmuliadi; Mansor, Fadillah (Online Journal of Islamic Management and Finance (OJIMF), 2021)
This study aimed to approve that continuous improvement is one of the important factors in our world today. As response for the development in business area, also clarifies a volume of them by organizations or companies, whether public or industrial, that lead to increase the company ranking. To achieve the desired goal, the previous study was done to identify the definition of improvement and the competition and the relationship between them. Research knowing that this image appears in our gallery of light on continuous improvement technology.